Fabrication of MPI-traceable alginate magnetic millirobots with multimodal selective-locomotion and heating capabilities - Armando Ramos-Sebastian; Ja-Sung Lee; Won-Il Song; Dong-Min Ji; So-Jung Gwak; Sung Hoon Kim (International Journal of Extreme Manufacturing)
Alginate-based magnetic micro/millirobots have demonstrated significant potential for biomedical applications due to their flexible structures and capacity to carry various types of cargo, such as cells, enabling targeted therapy to specific diseased regions within the body. Their active therapy is typically achieved through magnetic actuation and magnetic heating, while monitored by medical imaging methods like CT which pose additional risks due to radiation exposure. In the last decades, a novel imaging method for superparamagnetic materials, known as magnetic particle imaging (MPI), has been under active development, offering not only positional tracking but also the ability to measure concentration and temperature. Here, we report the world’s first MPI-traceable magnetic hydrogel robots, which employ a combination of iron oxide nanoflowers, NdFeB powder, and calcium alginate. Unlike previous magnetic alginate robots composed of a single magnetic material, the synergistic combination of NdFeB and nanoflowers enables these robots to exhibit triple magnetic functionalities: magnetic heating, locomotion at low magnetic fields, and tracking, all of which can be controlled using a single all-in-one electromagnetic coil system. The effects of various magnetization fields, as well as different concentrations of NdFeB and nanoflowers on the robots’ magnetic properties were analyzed. This led to the development of three types of triple-function robots (spiral, droplet, and hybrid), with experimental results demonstrating biocompatibility, a magnetic heating temperature increase of over 10 ºC in plasma fluid under a magnetic field of 13 kA·m ^‒1 at 200 kHz, locomotion speeds of up to 25 mm·s ^‒1 in fields below 2 mT, and an MPI tracking error of 2.8 mm with a selection field of 0.4 mT·mm ^‒1 . Additionally, the robots’ capacity for localized thermal therapy and selectively targeted cell delivery, as well as their locomotion within a medical phantom against a maximum flow of 50 mm·s ^‒1 were demonstrated.